POLA PEMBERIAN MP-ASI DINI PADA BAYI USIA 0-6 BULAN: STUDI TENTANG PENGETAHUAN DAN DUKUNGAN KELUARGA - Isnaeny, Isnaeny; Nursyam, Dian Eka; Nordianiwati, Nordianiwati; Noorma, Nilam; Titisari, Ira (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on the results of an initial survey conducted on 20 mothers who had babies aged 0-6 months, 8 babies (40.0%) were given formula milk, 6 babies (30%) were given honey and bananas, and 3 mothers (15%) did not want to give their breast milk. Furthermore, interviews were conducted with mothers regarding exclusive breastfeeding, as many as 8 mothers (40%) had insufficient knowledge, 5 mothers (25%) did not provide exclusive breastfeeding because they were hindered by work, and 7 mothers (35%) said that the family did not provide support in providing exclusive breastfeeding. The purpose of the study was to determine the relationship between maternal knowledge and family support for early complementary feeding in infants aged 0-6 months. The type of research is quantitative with a cross sectional approach. The research was conducted at the Minas Health Center work area in 2022. The sample amounted to 100 people. The results showed there was a relationship between maternal knowledge (p valu 0.020) and family support (p value 0.06) with early breastfeeding. It is recommended for pregnant women and breastfeeding mothers to always pay attention to the fulfillment of nutrition from pregnancy to the postpartum period as an effort to fulfill the smooth production of breast milk.Keywords: Breast milk, family, Knowledge